Unplugged: A Guide to Taming Technology Addiction for High School Students - Boateng, R. (Office of Research, Innovation and Development, University of Ghana, Legon., 2023)
In the digital age, finding a healthy balance with technology is crucial, especially for high school students. Unplugged is a comprehensive guide that empowers students to navigate the complexities of technology addiction and regain control over their digital lives. Packed with practical strategies, insightful questions, and real-life scenarios, this book offers a roadmap to breaking free from the grips of technology and cultivating a mindful relationship with it. From recognizing the signs of addiction and planning a digital detox to building healthy online habits and seeking support, Unplugged provides the tools needed to embrace technology wisely and create a positive impact in the digital world. Whether you're a student seeking a healthier tech-life balance or an educator looking to support your students, this book is an essential resource for understanding, addressing, and overcoming technology addiction.
Book
Keywords: Taming Technology Addiction; High School Students